Financial constraints and firm post-entry performance - Brito, Paulo (1995)
Firms finance production by internally generated funds and external loans. The benefits of leverage, however, come with a cost. This cost is related to the uncertainty banks face about the firm's quality and output price. As time evolves banks learn about the firm and adjust the terms of the loan contract. Because of this, firms do not have equal access to credit: small, young firms face greater binding debt constraints than more mature firms with well-known prospects. The firm survival rate, as well as the firm rate of growth, are, therefore, important issues in analyzing firm post-entry performance.